Export Diversification and Economic Growth in Nigeria - Philip Ifeakachukwu Nwosa; Fasina Oluwadamilola Tosin; Ogbuagu Matthew Ikechukwu (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2019)
The issue of export diversification has been contentious in Nigeria due to the country’s unstable growth pattern which is majorly associated with instability in the international oil market and the poor performance of other sectors of the economy. Therefore, this study examines the link between export diversification and economic growth in Nigeria from 1962 to 2016. The study utilizes the Auto-regressive Distributed Lag (ARDL) technique. The result of this study shows that export diversification has a positive but insignificant influence on economic growth in Nigeria. The above result implies that the oil sector still dominates the Nigerian economy while the diversification drive of the government has not been significant in other sectors of the economy. Thus, the study recommends the need for conscious economic policies that would promote the diversification of the entire non-oil sector of the economy. The study concludes that export diversification is an insignificant determinant of economic growth in Nigeria.